ANALYSIS OF MATHEMATICAL PROBLEM SOLVING SKILLS BASED ON TRENDS IN INTERNATIONAL MATHEMATICS AND SCIENCE STUDY (TIMSS) (International Conference on Elementary Education, 2018)
The purpose of this research is to determine the level of problem-solving ability and a mistake in doing mathematical problem solving test based on Trends in International Mathematics and Science Study (TIMSS) on Integrated Islamic Junior High School (SMPIT) in Bandung. The method used in this study was a survey with a qualitative-quantitative descriptive approach. The population was the 2nd grade students from three schools of SMPIT which represents the category of top, middle and bottom. The data collection technique using is test, interview and documentation. The results showed that (1) Based on the TIMSS assessment categories as much as 64% of students are still in the low category, moderate 9%, 9% higher and 26% is very high. (2) Mistaken done by the student because (a) a lack of understanding of the mathematical problem in understanding the problem and troubleshooting steps, (b) students are not accurate in the calculation, (c) problem solving strategy is less precise, and (d) student does not check re-count results.We conclude that the level of problem solving ability of students SMPIT in Bandung is still low.